The Moral Dissociation Curve, Blind Spots and Prescribing Death in Canada - Sams II, Richard (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2024)
Provider assisted death is becoming a leading cause of death in Canada since the passage of Medical Assistance in Dying (MAiD) legislation in 2016. What was to be exceptional has now become common; some are calling for it to be expected. Increasing numbers of patients with chronic, non-terminal conditions are being euthanized. Healthcare personnel are now approving and offering MAiD to vulnerable patients who are depressed, disabled, chronically ill or impoverished. This paper presents a rationale from a transcendent moral law perspective, traditionally called natural law, for why Canada now has the most liberal euthanasia regime in the world. The act of euthanasia requires the provider to willfully end the life of the patient by administering a lethal substance. This violates the transcendent moral law, do not kill. Once a culture willfully rejects this fundamental law and embraces a utilitarian ethic devoid of any principle except the notion of autonomy, it is inevitable that the practice will lead to ethical ambiguity and uncertainty. As the practice persists and becomes the norm, moral blindness develops which leads to gross abuses to human beings. I present an ethical diagram, the Moral Dissociation Curve, that depicts the reason for the trends unfolding in Canada. The Canadian healthcare system must re-affirm the principles of the Hippocratic Ethic and the inherent dignity of their patients. Those in healthcare need to prioritize high quality, compassionate, palliative care and say “no” to willfully ending the lives of suffering patients. In so doing, moral clarity will be re-gained, and society’s most vulnerable will be protected.